Portrait of Periodontal Disease Risk Factors among Adults - Prihastuti, Rieski; Pramono, Dibyo (Jurnal Kesehatan Masyarakat, 2024)
Periodontal disease is still a common oral disease all over the world. The yearly report from the Wonosobo District Health Office revealed that 17,807 out of 780,667 people had dental problems, with 5,422 of them having periodontal disease. This number was higher compared to the national number in Central Java Province. The aim of the study was to identify periodontal disease risk factors. Cross-sectional study was conducted using subjects aged 20-50 years old and resided in Wonosobo District. Data were analyzed using chi-square and logistic regression. A total of 440 subjects were included in the study. Independent variables consisted of demographic and oral condition namely sex, age group, education level, economic status, smoking, salivary flow rate, plaque accumulation, crowded tooth, and oral hygiene. The result of the study indicated that higher education level (OR 2.09; 95% CI 1.266-3.463) and lower plaque accumulation (OR 3.61; 95% CI 2.310-5.640) were found to be significant risk factors, whereas uncrowded teeth (OR 0.54; 95% CI 0.342-0.852) and good oral hygiene (OR 0.07; 95% CI 0.036-0.152) and fair oral hygiene (OR 0.28; 95% CI 0.142-0.572) were found to be significant protective factor for the occurrence of periodontal disease among adults in Wonosobo District.